PENGEMBANGAN APLIKASI REGISTRASI RAWAT JALAN PASIEN RSUD MENGGUNAKAN PERANGKAT ANDROID - Hadiprakoso, Raden Budiarto (JATI (Jurnal Mahasiswa Teknik Informatika), 2021)
In the last decade, technology has developed very rapidly, one of which is smartphones. The rapid development of smartphone technology has produced benefits for humans. These benefits include ease of access, efficiency, effectiveness, and convenience in carrying out daily activities. With this online doctor consultation application, patients do not need to go to the puskesmas or hospital when they are going to carry out a consultation. Especially in this COVID-19 pandemic, it will be very dangerous if the patient has to travel out of the house. This application is built on the android platform, using the android studio editor. The research method used is a model prototyping technique. Prototyping is development that is carried out quickly and tests prototypes of applications that are being developed and through interactions and iterative processes. By using the Java programming language on android studio and using the firebase realtime database. For the sample of observation data used is the Regional General Hospital (RSUD) Soedarso, Pontianak, West Kalimantan with an implementation time of June to July 2021. The result is a prototype version 1.0 has been developed with features in the form of patient registration, view doctor's schedule, queue messages and online doctor consultation